SUPPORTING LOCATION FACTORS TOWARDS SALAK AGROINDUSTRIAL DEVELOPMENT IN SLEMAN AGROPOLITAN DISTRICT - Abimanyu Putra Azhari; Kusumastuti Kusumastuti; Isti Andini (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2015)
Agropolitanconsept is developed as critics of industrial development failure in several Asian development countries which caused by high urbanization, unequal incomeand depletion of resources (Friedmann and Douglass, 1975). This consept also emphasize in agroindustrial development as part of successful agropolitan. Slemanagropolitan district has developed competitive commodites such as salak which can be process to high value products. AfterSlemanAgropolitan District established, the agroindustrial development still has not give the contribution for it. Many industries have limited quantity and there is no connection among other industries, so the industries just walked by itself. Many of them do not observe the important thing on their development, like location. Location has an important role for sustaining agroindustrial development. Based on this issues, the research goal is the achievement value of supporting location factors to salakagroindustrial development in SlemanAgropolitan District. The method is scoring analysis in every location factors variable in agroindustrial development to find the value achivement of supporting location factors.The result of this research, location factors have strongly support for salakagroindustrial development in SlemanAgropolitan District. Raw identified through origin, distance and how to gather the raw has value 96,4% which means strongly support. Labour identified through quantity, origin and distance has value 66,9% which means support. Market identified through origin, distance and how to distribute has value 90,6% which means strongly support. Transportation/accesibility identified through road, transportation cost and time has value 84,2% which means strongly support. Land identified through topography and disasten vulnerability has value 97,5% which means strongly support for agroindustrial development. Keywords:agropolitan, agroindustrial development, location factor